2012
DOI: 10.1055/s-0039-3401672
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar hump of right hepatic artery: incidence and surgical significance

Abstract: Background and aims : The right hepatic artery occasionally forms a sinuous tortuousity called as caterpillar hump or Moynihan's hump, which occupies the major portion of Calot's triangle. Due to this variation, inadvertent injury to right hepatic artery may occur during surgical procedures. The aim of the study is to find out the incidence of Caterpillar hump of right hepatic artery in cadavers and to correlate with surgical significance. Materials and methods : Sixty cadavers allotted for the purpose of teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Nine studies[131521222324252627] reported data from a total of 498 human cadavers used for anatomical dissection purpose ranging from 1[21] to 90[22] specimens per study; six studies[12028293031] performed the research on a total of 579 patients submitted to cholecystectomy for symptomatic cholelithiasis, ranging from 1[129] to 200[28] patients per study [Table 1]. Only the study by Benson and Page[32] involved 140 patients submitted to cholecystectomy and 65 human cadavers as well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies[131521222324252627] reported data from a total of 498 human cadavers used for anatomical dissection purpose ranging from 1[21] to 90[22] specimens per study; six studies[12028293031] performed the research on a total of 579 patients submitted to cholecystectomy for symptomatic cholelithiasis, ranging from 1[129] to 200[28] patients per study [Table 1]. Only the study by Benson and Page[32] involved 140 patients submitted to cholecystectomy and 65 human cadavers as well.…”
Section: Resultsmentioning
confidence: 99%
“…Only the study by Benson and Page[32] involved 140 patients submitted to cholecystectomy and 65 human cadavers as well. The majority of studies were conducted in single Eastern centres (188 cholecystectomies, 32.5% and 308 cadavers, 61.8%) (India, Saudi Arabia, Pakistan, Iraq, Japan),[11315202122232426272930] while the five others were performed in the Western and American Countries (391 cholecystectomies, 67.5% and 190 cadavers, 38.2%) (United Kingdom, Yugoslavia, Croatia, USA). [2225283132]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Presence of tortuous right hepatic artery (caterpillar hump) may lead to vascular injuries during surgical procedures in this region as such an artery is closer to the cystic duct and the cystic artery is short. It is important for surgeons to know this variant to avoid inadvertent ligation of right hepatic artery CONCLUSION instead of cystic artery, thereby preventing vascular injuries and the fatal ischaemic necrosis of right lobe of the liver [23].…”
Section: Discussionmentioning
confidence: 99%